Kepemimpinan perpustakaan sekolah di era digital - M.Aqiel Haiqal (UIN Sumatera Utara, 2016)
The library is an important place in education and teaching programs. Where the principal, head of libraries and related parties holds a very important role for the success of the school library. Librarian as cogs required dedicated and devoted in serving to enhance the role of the school library. With the advancement of technology librarians should improve the quality and sensitivity of the progress that has to do with development and service improvement.